The Evolutionary Development of CAI Evaluation Approaches - Avner, R. A. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1975)
The role of evaluation in the development of evolutionary procedures is briefly described and highlighted. Four aspects of evaluation technique which distinguish efficient from inefficient CAI programs are identified. Evaluation of products is also characterized. Findings of a continuing survey of students via questionnaire as to the value of certain courseware are listed. (SK)
ERIC Note: Paper presented at the Annual Meeting of the American Educational Research Association (Washington, D.C., March 30, 1975 through April 3, 1975).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Computer Assisted Instruction; Educational Development; Educational Innovation; Educational Media; Educational Planning; Educational Research; Evaluation Methods; Instructional Design; Media Research; PLATO; Evolutionary Development Program; Speeches/Meeting Papers